Importance of Normalization of Carbohydrate Antigen 19-9 in Patients With Intrahepatic Cholangiocarcinoma - Li, Hui; Feng, Yuan; Liu, Chang; Li, Jiawang; Li, Jiaxin; Wu, Hong; Wang, Genshu; Li, Dewei (Frontiers in Oncology, 2021)
Background: Although carbohydrate antigen 19-9 (CA19-9) is an established prognostic marker for intrahepatic cholangiocarcinoma (ICC) patients, the significance of elevated preoperative CA19-9 that normalized after resection remains unknown. This study aimed to investigate whether elevated preoperative CA19-9 that normalized after curative resection had an impact on prognosis among patients with ICC. Methods: Patients who underwent curative resection for stage I to III ICC between 2009 and 2018 were identified. Patients were categorized into three cohorts: normal preoperative CA19-9, elevated preoperative CA19-9 but normalized postoperative CA19-9, and persistently elevated postoperative CA19-9. Overall survival (OS), recurrence-free survival (RFS) and hazard function curves over time were analyzed. Results: A total of 511 patients (247 [48.3%] male; median age, 58 years) were included. Patients with elevated preoperative CA19-9 (n=378) were associated with worse RFS and OS than those with normal preoperative CA19-9 (n=152) (both P < 0.001). Patients with persistently elevated postoperative CA19-9 (n=254) were correlated to lower RFS and OS than the combined cohorts with normal postoperative CA19-9 (n=257) (both P < 0.001). The hazard function curves revealed that the risk of recurrence and mortality peaked earlier and higher in elevated postoperative CA19-9 group than the other 2 groups. Multivariate analyses identified persistently elevated, rather than normalized postoperative CA19-9 as independent risk factor for shorter RFS and OS in ICC. Conclusions: Elevated preoperative serum CA19-9 that normalizes after curative resection is not an indicator of poor prognosis in ICC. Patients with persistently elevated postoperative CA19-9 are at increased risk of recurrence and death.